Enhancing Junior High School Student’s English Speaking Skill through Problem-Based Learning - Lestari, Endang; Nurwahyuni, Oktria; Al Arfan, Adam (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study examines the effectiveness of Problem-Based Learning (PBL) in improving Junior High School students’ English speaking skills. The research was motivated by students’ low speaking achievement, particularly in expressing likes and dislikes. A Classroom Action Research design based on the Kemmis and Taggart model was employed, comprising planning, action, observation, and reflection phases. The participants were 20 seventh-grade students. Data were collected through classroom observations, documentation, and field notes, and analyzed using descriptive quantitative methods. The findings indicate a steady improvement in students’ speaking performance across research cycles. In the pre-cycle phase, only 30% of students met the minimum mastery criterion, with an average score of 63.5. This figure increased to 50% in Cycle I and reached 90% in Cycle II, exceeding the predetermined success criterion of 80%. The results demonstrate that the implementation of PBL significantly enhances students’ English speaking skills. In addition to improving learning outcomes, PBL fostered students’ critical and analytical thinking, self-confidence, pronunciation accuracy, intonation, and speaking fluency. These findings suggest that PBL is an effective instructional model for developing speaking competence in English language learning.